Dual tuning effect of epoxy-to-curing agent ratio and PKS-based activated carbon loading on the mechanical and self-healing performance of epoxy vitrimer composites - Lee, Chuan Li; A. Bakar, Balkis Fatomer; Chin, Kit Ling; Abdullah, Luqman Chuah; Idris, Nurul Izzaty; Chang, Qi Ren (John Wiley and Sons, 2025)
This study investigates the dual tuning of epoxy-to-curing agent ratios (1:1.4, 1:1.6, 1:1.8) and palm kernel shell (PKS) derived activated carbon loadings (0.5, 1.0, 1.5 wt%) to improve the thermal, mechanical, and self-healing performance of epoxy vitrimer composites. A key novel finding of this study is that the bio-based PKS derived activated carbon acts as a dual-functional filler, serving both as a mechanical reinforcing phase and a chemical modifier, where its high surface area provides reinforcement, enhancing interfacial adhesion, load transfer, and crosslink network stability. Incorporation of this functional filler also intensified N.H and Si.O.Si signals, indicating robust amine-epoxy crosslinking and the formation of dynamic siloxane networks, which enable thermally activated self-healing and achieve 85%–88% strain recovery over multiple cycles while allowing the network to reorganize for repeated healing and reshaping. FESEM revealed a porous, amorphous structure that promotes crack bridging and stress redistribution, supporting both mechanical reinforcement and self-healing performance. Dynamic mechanical analysis (DMA) revealed a dual glass transition in the composite with 1.0 wt% filler and a 1:1.6 ratio, where the first T g (85.8°C) corresponds to a softer matrix and the second (95.1°C) corresponds to a rigid interfacial zone, balancing stiffness and energy dissipation. This sample also exhibited the highest storage modulus (1710 MPa) and lowest damping factor (1.47) due to strong filler–matrix interactions. This research also found that by increasing filler content and curing agent ratio enhances self-healing due to improved chain mobility, but excessive filler can lead to agglomeration, which restricts tensile strength, emphasizing the need to balance filler loading to maintain both mechanical performance and healing efficiency. Together, these results demonstrate that dual tuning combined with dual-functional PKS filler allows vitrimer composites to be tailored for a desired balance of structural reinforcement, dynamic adaptability, and self-healing, offering flexibility in designing high-performance, sustainable materials.